2007
DOI: 10.1017/s0959270907000846
|View full text |Cite
|
Sign up to set email alerts
|

Ranging behaviour of Cape Vultures Gyps coprotheres from an endangered population in Namibia

Abstract: SummaryThe Cape Vulture (Gyps coprotheres) is an obligate cliff-nesting vulture endemic to southern Africa. Its range and population size have declined markedly over the last century. Namibia has just one colony, located on the cliffs of the Waterberg Plateau, with a population estimated to be eight adult birds, including two females. The species is regarded as Critically Endangered in Namibia, and establishing a secure breeding population may require intensive management. Data on movements, foraging range and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 8 publications
7
75
2
Order By: Relevance
“…For example, Xirouchakis & Andreou (2009) reported range sizes ranging from 390 to 1300 km 2 (according to 100% MCP), and 380 km 2 -64 km 2 according to 95% and 50% kernel, respectively; whereas Gil et al (2009) reported maximum home-ranges between 23-161 km 2 . By contrast, the home-range size reported here was lower than those reported for satellite-tracked Cape Vultures Gyps coprotheres in Namibia, which were 21320 km 2 for adults and 482276 km 2 for juveniles (Bamford et al 2007). Differences in home-range size could be explained by the availability of suitable habitat for foraging, individual's age and sex, as well as the method used for tracking.…”
Section: Discussioncontrasting
confidence: 90%
“…For example, Xirouchakis & Andreou (2009) reported range sizes ranging from 390 to 1300 km 2 (according to 100% MCP), and 380 km 2 -64 km 2 according to 95% and 50% kernel, respectively; whereas Gil et al (2009) reported maximum home-ranges between 23-161 km 2 . By contrast, the home-range size reported here was lower than those reported for satellite-tracked Cape Vultures Gyps coprotheres in Namibia, which were 21320 km 2 for adults and 482276 km 2 for juveniles (Bamford et al 2007). Differences in home-range size could be explained by the availability of suitable habitat for foraging, individual's age and sex, as well as the method used for tracking.…”
Section: Discussioncontrasting
confidence: 90%
“…It seems reasonable to assume that Cape Vultures achieve lower take-off angles than White-backed Vultures, and this would mean that some carcasses that were available to White-backed Vultures would not be available to Cape Vultures. Of the factors put forward to explain the decline in African vulture populations, the runway hypothesis is the only one so far shown to affect species differently, perhaps explaining why, for example, the Namibian population of the Cape Vulture is declining (Bamford et al 2007), while that of the White-backed Vulture in the area is flourishing. …”
Section: Discussionmentioning
confidence: 99%
“…It is commonly unselective and there is little evidence of cost-effective diminution of livestock losses (Treves & Naughton-Treves, 2005;Berger, 2006), as predators learn to avoid control efforts (Brand et al, 1995;Knowlton et al, 1999). Methods such as leg-hold traps, snaring and poisoning are largely indiscriminate and often kill non-target species (Rochlitz et al, 2010); in South Africa, this includes threatened species such as Cape vultures Gyps coprotheres (Bamford et al, 2007). Unintended outcomes of removing territorial predators can include an influx of replacement individuals, potentially increasing the local predator population and the risk of depredation (Crooks & Soulé, 1999;Knowlton et al, 1999), through what are known generically as perturbation effects (Tuyttens & Macdonald, 2000).…”
Section: Introductionmentioning
confidence: 99%